Insight into metabolic sensors of nitrosative stress protection in Phytophthora infestans - Gajewska, Joanna; Floryszak-Wieczorek, Jolanta; Kosmala, Arkadiusz; Perlikowski, Dawid; Żywicki, Marek; Sobieszczuk-Nowicka, Ewa; Judelson, Howard S.; Arasimowicz-Jelonek, Magdalena (Frontiers in Plant Science, 2023)
Phytophthora infestans, a representative of phytopathogenic oomycetes, have been proven to cope with redundant sources of internal and host-derived reactive nitrogen species (RNS). To gain insight into its nitrosative stress resistance mechanisms, metabolic sensors activated in response to nitrosative challenge during both in vitro growth and colonization of the host plant were investigated. The conducted analyses of gene expression, protein accumulation, and enzyme activity reveal for the first time that P. infestans (avirulent MP946 and virulent MP977 toward potato cv. Sarpo Mira) withstands nitrosative challenge and has an efficient system of RNS elimination. The obtained data indicate that the system protecting P. infestans against nitric oxide (NO) involved the expression of the nitric oxide dioxygenase (Pi-NOD1) gene belonging to the globin family. The maintenance of RNS homeostasis was also supported by an elevated S-nitrosoglutathione reductase activity and up-regulation of peroxiredoxin 2 at the transcript and protein levels; however, the virulence pattern determined the expression 2 abundance. Based on the experiments, it can be concluded that P. infestans possesses a multifarious system of metabolic sensors controlling RNS balance via detoxification, allowing the oomycete to exist in different micro-environments flexibly.